2018
DOI: 10.7754/clin.lab.2017.170803
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Implications of Thrombelastography in the Diagnosis of Acute Cerebral Infarction

Abstract: TEG results have important clinical implications in the early diagnosis of acute cerebral infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Mild cases of cerebral infarction can be completely asymptomatic, but they can also manifest as recurrent limb paralysis or dizziness, which is known as a transient ischemic attack. Individuals with severe cases of cerebral infarction may not only experience limb paralysis, but acute coma and death may also occur in some cases ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mild cases of cerebral infarction can be completely asymptomatic, but they can also manifest as recurrent limb paralysis or dizziness, which is known as a transient ischemic attack. Individuals with severe cases of cerebral infarction may not only experience limb paralysis, but acute coma and death may also occur in some cases ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 In human patients with liver disease, stroke, neoplasia, or in those undergoing surgery, TEG parameters can predict the occurrence of thrombosis. 40 , 41 , 42 , 43 , 44 , 45 In dogs, indirect evidence for an association of high TEG G values with thrombosis comes from the observation that conditions associated with thrombosis, such as immune‐mediated hemolytic anemia, protein‐losing enteropathy, protein‐losing nephropathy, hyperadrenocorticism, and pancreatitis, have TEG parameters compatible with hypercoagulabilty. 36 , 46 Studies that link potential coagulation biomarkers of hypercoagulability in dogs with GBM with actual indices of clinical thrombosis are needed, but will be hampered by the difficulty of making an antemortem diagnosis of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have suggested a correlation, 36,37 others have failed to show TEG abnormalities in dogs with confirmed thrombosis 38,39 . In human patients with liver disease, stroke, neoplasia, or in those undergoing surgery, TEG parameters can predict the occurrence of thrombosis 40‐45 . In dogs, indirect evidence for an association of high TEG G values with thrombosis comes from the observation that conditions associated with thrombosis, such as immune‐mediated hemolytic anemia, protein‐losing enteropathy, protein‐losing nephropathy, hyperadrenocorticism, and pancreatitis, have TEG parameters compatible with hypercoagulabilty 36,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that the death/disability rate of ACI within 1 year is high, which is seriously harmful to people's health 2 . The diagnosis and treatment mainly focus on early detection, treatment and prevention 3,4 . There have been studies on the diagnostic value of C‐reactive protein and interleukin‐6 in ACI, but their specificity is not high 3–5 .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis and treatment mainly focus on early detection, treatment and prevention 3,4 . There have been studies on the diagnostic value of C‐reactive protein and interleukin‐6 in ACI, but their specificity is not high 3–5 . At present, the diagnosis of ACI depends on the Stroke Scale score, computed tomography (CT), magnetic resonance imaging (MRI) and other imaging methods 6 .…”
Section: Introductionmentioning
confidence: 99%